Decellularized Scaffolds for Skin Repair and Regeneration - Mélissa Dussoyer; Anna Michopoulou; Patricia Rousselle (Applied Sciences, 2020)
The skin is the largest organ in the body, fulfilling a variety of functions and acting as a barrier for internal organs against external insults. As for extensive or irreversible damage, skin autografts are often considered the gold standard, however inherent limitations highlight the need for alternative strategies. Engineering of human-compatible tissues is an interdisciplinary and active field of research, leading to the production of scaffolds and skin substitutes to guide repair and regeneration. However, faithful reproduction of extracellular matrix (ECM) architecture and bioactive content capable of cell-instructive and cell-responsive properties remains challenging. ECM is a heterogeneous, connective network composed of collagens, glycoproteins, proteoglycans, and small molecules. It is highly coordinated to provide the physical scaffolding, mechanical stability, and biochemical cues necessary for tissue morphogenesis and homeostasis. Decellularization processes have made it possible to isolate the ECM in its native and three-dimensional form from a cell-populated tissue for use in skin regeneration. In this review, we present recent knowledge about these decellularized biomaterials with the potential to be used as dermal or skin substitutes in clinical applications. We detail tissue sources and clinical indications with success rates and report the most effective decellularization methods compatible with clinical use.